An Evaluation of Improvement Plans Bridge Abutment Penaga in Bintan Island - Rasyid Khoirul M; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2023)
The bridge is a construction that connects one place to another. Generally, the bridge structure is divided into two, namely, the upper structure and the lower structure. The upper structure carries the load directly above the surface, while the lower structure carries the load received above and then transmits the load to the foundation layer on hard soil. In the bridge structure, one part has a unique dual role in supporting the load on its surface, namely the abutments. The abutments are located at both ends of the bridge pillars, which aim to carry the live and dead loads on the bridge. Usually, a support bridge is built at the end of the bridge located on the riverbank with an important role in maintaining the bridge's stability. The method used in this study is the quantity method and literature review. As for the process of processing data using search techniques and collecting information related to the research to be carried out. The purpose of this research is to repair the abutments that have been damaged by considering the rules according to the standards. The results of the analysis that has been carried out state that for structural stability, the abutments under normal conditions, when an earthquake occurs, can withstand maximum and minimum earth stress forces. So it can be concluded that the abutment structure can withstand the thrust that occurs at maximum and minimum conditions. While the results of the structural analysis of shear forces are stated to be unsafe because the strength of the bridge structure to withstand shear forces is less than the required safety factor based on national standard provisions. This research also provides information to the public for bridge users.